2017
DOI: 10.1093/aje/kwx332
|View full text |Cite
|
Sign up to set email alerts
|

Early-Pregnancy Plasma Concentrations of Perfluoroalkyl Substances and Birth Outcomes in Project Viva: Confounded by Pregnancy Hemodynamics?

Abstract: Associations of prenatal exposure to perfluoroalkyl substances (PFAS), ubiquitous chemicals used in stain- and water-resistant products, with adverse birth outcomes may be confounded by pregnancy hemodynamics. We measured plasma concentrations of 4 PFAS in early pregnancy (median length of gestation, 9 weeks) among 1,645 women in Project Viva, a study of a birth cohort recruited during 1999-2002 in eastern Massachusetts. We fitted multivariable models to estimate associations of PFAS with birth weight-for-gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 49 publications
9
101
4
Order By: Relevance
“…Two other studies estimated the prenatal PFOA exposure level through an assessment model and found no increased risk of preterm birth [25,26]. Likewise, our study showed no associations between PFAS and length of gestation, which was also consistent with most previous studies [16,17,19,21].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Two other studies estimated the prenatal PFOA exposure level through an assessment model and found no increased risk of preterm birth [25,26]. Likewise, our study showed no associations between PFAS and length of gestation, which was also consistent with most previous studies [16,17,19,21].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, nearly 1.5-fold odds of PTB was found for per doubling increase of perfluoroheptane sulfonate (PFHpS) and perfluorodecanoic acid (PFDA) concentrations in the Danish study [17]. A 1.2-fold risk of PTB was reported for per interquartile range of perfluorononanoic acid (PFNA) in the U.S. study [16]. Chen et al also found that a higher level of PFOS but not PFOA in the cord blood was associated with an increased risk of PTB (odds ratio: 2.5, 95% CI: 1.5, 4.1) [18].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…30,31 Timing of prenatal exposure measurements Sampling for chemical analyses early in pregnancy may be important not only to establish an early developmental effect of PFAS exposure but also to avoid the potential of confounding due to pregnancy-related changes in the glomerular filtration rate and hemodynamics. 3,32 A recent meta-analysis by Steenland et al suggests that the timing of exposure measurement is critically important for the association between maternal PFOA serum concentrations and offspring BW. 6 Sampling later in pregnancy may be related to more problems with confounding or reverse causality issues.…”
Section: Different Associations In Girls and Boysmentioning
confidence: 99%
“…The Project Viva birth cohort in Massachusetts used anthropometric and dual X-ray absorptiometry to measure fat mass, fat-free mass and trunk fat mass indexes and associated maternal prenatal PFASs levels with higher BMI and a total fat mass index in mid-childhood among girls [37]. Also, they found associations of early-pregnancy PFOS and PFNA levels with reduced birth weight-for-gestational-age z scores, and adjusting for markers of pregnancy hemodynamics (glomerular filtration rate and plasma albumin) as potential confounders did not materially impact the associations observed [23]. A Danish study examined prenatal exposure to PFASs and risk of being overweight at 20 years of age and found that only maternal PFOA was positively associated with being overweight or obesity and higher waist circumference among female, but not male offspring [39].…”
Section: Fetal and Postnatal Growthmentioning
confidence: 99%